Microalgae-based biogas slurry treatment integrated with sustainable aviation fuel production: from waste to high-value bio-jet fuel - Binbin Zhu; Hongyin Chen; Jing Lv; Wenjun Zhang; Jiaming Liu; Ruirui Liu; Bishu Qi; Shuhui Li; Chengyu Yang; Xiao Yan; Zijian Xia; Xingliang Xu; et al. (Bioresource Technology, 2026)

Selective cleavage of Cβ-O-containing Cα-Cβ bond on Cu-Ni3S2 for electrocatalytic glycerol oxidation to formic acid - Ruirui Xu; Xinti Yu; Ce Fu; Lina Li; Zhangxing Chen; Heng Zhao (Chemical Engineering Journal, 2026)

Indium-doped CuSnO3 perovskite hybrids for chemiresistive CO sensing - Linyan Gu; Yangtao Qian; Yiting Liu; Miao Cheng; Tao Wei; Qianqian Liu; Ruirui Wang; Wanfei Li; Zhenxiao Fu; Haiyang Jiang; Zibo Li; Bo Liu; et al. (Chemical Engineering Journal, 2026)

Resveratrol mitigates diabetes-induced cardiac dysfunction via SIRT1/PPAR-α/PGC-1 pathway - Ruirui Fu; Ju Hao (Molecular Genetics and Genomics, 2025)

Synthesis and biological evaluation of triazole alcohols containing an indole-3-methyl(phenyl)amino side chain against fluconazole-resistant Candida albicans - Zefei Fan; Lijiao Yang; Jidong Wang; Yafei Hou; Fei Zou; Tianyu Zhang; Yongyan Fu; Yue Zhang; Ruirui Wang; Shichong Yu; Guanghui Ni (Medicinal Chemistry Research, 2025)

Auxiliary electrodialysis realizes over 50 times concentration of nuclide ions from liquid effluents of nuclear power plants - Zhenzhen Cui; Baoying Wang; Ruirui Li; Zihao Wang; Weicheng Fu; Junying Yan; Liang Wu; Yaoming Wang; Tongwen Xu (Desalination, 2025)

Mechanisms and characterization of interzone mass transfer inhomogeneity in PEM fuel cells - Huicui Chen; Enyang Shi; Ruirui Zhang; Peng Ren; He Wang; Zijing Zhu; Xi Fu; Pucheng Pei (Chemical Engineering Journal, 2024)

Shared xerophytic genes and their re‐use in local adaptation to aridity in the desert plant Gymnocarpos przewalskii - Ruirui Fu; Yuxiang Zhu; Ying Liu; Zhaoping Yang; Ruisen Lu; Yingxiong Qiu; Martin Lascoux; Pan Li; Jun Chen (Molecular Ecology, 2024)
In order to thrive and survive, plant species need to combine stability in the long term and rapid response to environmental challenges in the short term. The former would be reflected by parallel or convergent adaptation across species, and the latter by pronounced local adaptation among populations of the same species. In the present study, we generated a high‐quality genome and re‐sequenced 177 individuals for Gymnocarpos przewalskii , an important desert plant species from North‐West China, to detect local adaptation. We first focus on ancient adaptation to aridity at the molecular level by comparing the genomic data of 15 species that vary in their ability to withstand aridity. We found that a total of 118 genes were shared across xerophytic species but absent from non‐xerophytic species. Of the 65 found in G. przewalskii , 63 were under purifying selection and two under positive selection. We then focused on local adaptation. Up to 20% of the G. przewalskii genome showed signatures of local adaptation to aridity during population divergence. Thirteen of the selected shared xerophytic genes were reused in local adaptation after population differentiation. Hence, only about 20% of the genes shared and specific to xerophytic species and associated with adaptation to aridity were later recruited for local adaptation in G. przewalskii .

Exosome-shuttled FTO from BM-MSCs contributes to cancer malignancy and chemoresistance in acute myeloid leukemia by inducing m6A-demethylation: A nano-based investigation - Ruirui Kou; Tian Li; Caizhu Fu; Duanfeng Jiang; Yue Wang; Jie Meng; Ruilan Zhong; Changjiu Liang; Min Dong (Environmental Research, 2024)

Fabrication and application of molecularly imprinted polymer doped carbon dots coated silica stationary phase - Peijun Chai; Xuhui Geng; Ruirui Zhu; Wenpu Wu; Xuesong Wang; Jinhua Li; Longwen Fu; Hongdan Wang; Wanhui Liu; Lingxin Chen; Zhihua Song (Analytica Chimica Acta, 2023)

A cascade electro-dehydration process for simultaneous extraction and enrichment of uranium from simulated seawater - Ruirui Li; Huangying Wang; Junying Yan; Rong Fu; Baoying Wang; Chenxiao Jiang; Yaoming Wang; Tongwen Xu (Water Research, 2023)

A direct electrochemical substitution electrodialytic system for CO2 conversion into high value-added soda - Huangying Wang; Haiyang Yan; Kang Peng; Junying Yan; Rong Fu; Ruirui Li; Baoying Wang; Chenxiao Jiang; Yaoming Wang; Tongwen Xu (Chemical Engineering Journal, 2023)

Ion transmembrane behaviors in selective electrodialysis for acid recovery: Impact of ion categories - Junying Yan; Huangying Wang; Haiyang Yan; Ruirui Li; Rong Fu; Weicheng Fu; Liang Ge; Baoying Wang; Yaoming Wang; Tongwen Xu (Desalination, 2023)

Integrated miRNA-mRNA analysis reveals the dysregulation of lipid metabolism in mouse liver induced by developmental arsenic exposure - Xin Chen; Ruirui Wu; Hengchao Wu; Yuxin Hu; Huihui Wang; Jingqi Fu; Jingbo Pi; Yuanyuan Xu (Journal of Hazardous Materials, 2023)

Application of the CRISPR/Cas9 system in Dioscorea zingiberensis - Shan Feng; Wei Song; Ruirui Fu; Hong Zhang; Anran Xu; Jiaru Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)